Midwife Care on 3 Months Injected Kb Accepters With Spotting At The Angel Paropo Maternity Clinic - Ernita Ruslaini Caniago; Princess Ramadani; Nurainun; Intan Agustin (Institute of Computer Science (IOCS), 2022)
Based on the Indonesian Health Profile, the number and percentage of Indonesia's population for adolescents aged 10-19 years (WHO definition for adolescent) is 44 million or 21%, where the problems faced by many adolescents are reproductive health issues, premarital sex, unprotected pregnancy. It is hoped that the number of drug users, the number of people with STDs, HIV/AIDS and cases of abortion show quite worrying symptoms. Research has been carried out which aims to describe the knowledge of mothers who have teenage girls about sexual behavior and teenage pregnancy in the VIII Ward of Menistrim Village, Kec. East Binjai. This research is descriptive using primary data obtained through questionnaires submitted to respondents with a sample of 54 people. The study was conducted in August 2006. From the results of the study, it is known that the majority of 54 respondents are knowledgeable enough as much as 50%, where based on age, the majority are 40-60 years old and 73.91% have good knowledge, based on education the majority are secondary education and 66.6 % knowledgeable enough, and based on the majority of information sources from the mass media and 62.96% knowledgeable enough. In order to obtain better knowledge, it is hoped that mothers who have teenage girls seek correct information, namely from health workers about sexual behavior and teenage pregnancy. based on education the majority of secondary education and 66.6% have sufficient knowledge, and based on information sources the majority are from the mass media and 62.96% are moderately knowledgeable. In order to obtain better knowledge, it is hoped that mothers who have teenage girls seek correct information, namely from health workers about sexual behavior and teenage pregnancy. based on education the majority of secondary education and 66.6% have sufficient knowledge, and based on information sources the majority are from the mass media and 62.96% are moderately knowledgeable. In order to obtain better knowledge, it is hoped that mothers who have teenage girls seek correct information, namely from health workers about sexual behavior and teenage pregnancy.